A novel composite negative stiffness structure for recoverable trapping energy. (February 2020) - Chen, Shuai; Wang, Bing; Zhu, Shaowei; Tan, Xiaojun; Hu, Jiqiang; Lian, Xu; Wang, Lianchao; Wu, Linzhi
Abstract: Negative stiffness (NS) structures, as hopeful metamaterials, are potential in the energy absorption (EA) field. However, low specific energy absorption (SEA) limits its engineering application. In this paper, a novel reusable composite NS structure composed of Two-material systems is proposed and investigated. It is potential to be used in shock isolation, vibration control and deployable structure. Specimen was fabricated by additive manufacturing technology. Mechanical properties of this structure are studied with a combination of compression tests and simulations. Repeatability of the structure is then verified through cyclic compression. Besides, plate-impact tests were also carried out to study the cushion performance of this structure. The results of the impact tests reveal that the composite NS structure has good cushion performance by adjusting the threshold of acceleration response amplitude and completely reusable when the snap-through behavior occurs.